2015
DOI: 10.1371/journal.pone.0118920
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Features and Important Parameters of Large Optic Discs for Diagnosing Glaucoma

Abstract: PurposeTo compare the optic disc parameters of glaucomatous eyes to those of non-glaucomatous eyes with large discs.MethodsWe studied 225 consecutive eyes with large optic discs (>2.82 mm2): 91 eyes with glaucoma and 134 eyes without glaucoma. An eye was diagnosed with glaucoma when visual field defects were detected by the Humphrey Field Analyzer. All of the Heidelberg Retina Tomograph II (HRT II) parameters were compared between the non-glaucomatous and glaucomatous eyes. A logistic regression analysis of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 30 publications
(29 reference statements)
0
11
0
1
Order By: Relevance
“…Chauhan et al 20 demonstrated a decline of global mean BMO-MRW and RNFLT with age at a rate of −1.34 and −0.21 μm/year for BMO area ranging from 1.05 to 3.40 mm2. In a recent study by Vianna et al , healthy controls had a significant reduction of BMO-MRW (mean: −1.92 μm/year, p<0.01) and RNFLT (mean: −0.44 μm/year, p=0.01) 27.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chauhan et al 20 demonstrated a decline of global mean BMO-MRW and RNFLT with age at a rate of −1.34 and −0.21 μm/year for BMO area ranging from 1.05 to 3.40 mm2. In a recent study by Vianna et al , healthy controls had a significant reduction of BMO-MRW (mean: −1.92 μm/year, p<0.01) and RNFLT (mean: −0.44 μm/year, p=0.01) 27.…”
Section: Discussionmentioning
confidence: 99%
“…This study contributes to the current effort to compare margin-based rim area measurements from CSLT with BMO-based measurements from SD-OCT by analysing a group of non-glaucomatous eyes with very large optic discs, so-called macrodiscs (disc size >2.45 mm2 in CSLT). The aim of this study was to create a reference base to large ONHs in SD-OCT diagnostics of the ONH and to correlate CSLT with SD-OCT measurements.…”
Section: Introductionmentioning
confidence: 99%
“…Reason for this includes, that patients with large optic discs present physiologically a large irregular excavation of the optic nerve head. [1][2][3] Morphometric analysis of the optic nerve head (ONH) and visual field testing represent the major keystones in diagnosis, treatment planning and follow-up of glaucoma patients.…”
Section: Introductionmentioning
confidence: 99%
“…A histological study has reported that the micro-vascular bed of the disc is an integral part of the retina-optic nerve vascular system [42]. A clinical study reported that the MCD was significantly larger in glaucomatous eyes compared to non-glaucomatous eyes [43]. Considering that CRAE is a part of the retina-optic nerve vascular system, the association between deeper MCD and narrower CRAE in the population suggests a relationship between altered optic nerve head (ONH) blood flow and movement of the lamina region.…”
Section: Discussionmentioning
confidence: 99%